Peran Otomasi Pajak Berbasis API dalam Meningkatkan Kepatuhan UMKM: Studi Literatur - Made Riska Putri Astiyanti; Luh Putu Meri Saptiani; Dwi Suci Jayanti Nirmala; I Wayan Agus Parta Wijaya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The rapid evolution of digital technologies has fundamentally reshaped tax administration systems, particularly for Micro, Small, and Medium Enterprises (MSMEs), which constitute a critical driver of economic development yet continue to demonstrate suboptimal levels of tax compliance. This study aims to critically examine the role of Application Programming Interface (API)-based tax automation in enhancing MSME tax compliance through a systematic narrative literature review approach. Employing a qualitative design, this study synthesizes recent scholarly works published within the last five years to identify patterns, relationships, and emerging trends in digital taxation practices. The findings indicate that API-based automation significantly improves administrative efficiency, minimizes human error, and facilitates real-time data integration between taxpayer systems and tax authorities. Moreover, such integration enhances transparency and reduces compliance costs, thereby fostering voluntary compliance behavior among MSMEs. Nevertheless, the effectiveness of this technological intervention is contingent upon several structural and behavioral factors, including digital literacy, technological readiness, and the availability of reliable digital infrastructure. Persistent disparities in these areas may constrain the scalability and inclusiveness of API implementation. This study underscores that API-based tax automation represents a transformative policy instrument in modernizing tax administration systems, provided it is supported by coherent regulatory frameworks, capacity-building initiatives, and equitable infrastructure development. The findings contribute to the broader discourse on digital taxation by offering a conceptual foundation for developing adaptive and sustainable compliance strategies in the era of economic digitalization